A Comparison of Motor Unit Control Strategies between Two Different Isometric Tasks - Jeon, Sunggun (Int J Environ Res Public Health, 2020)
Background: This study examined the motor unit (MU) control strategies for non-fatiguing isometric elbow flexion tasks at 40% and 70% maximal voluntary isometric contraction. Methods: Nineteen healthy individuals performed two submaximal tasks with similar torque levels: contracting against an immovable object (force task), and maintaining the elbow joint angle against an external load (position task). Surface electromyographic (EMG) signals were collected from the agonist and antagonist muscles. The signals from the agonist were decomposed into individual action potential trains. The linear regression analysis was used to examine the MU recruitment threshold (RT) versus mean firing rates (MFR), and RT versus derecruitment threshold (DT) relationships. Results: Both agonist and antagonist muscles’ EMG amplitudes did not differ between two tasks. The linear slopes of the MU RT versus MFR and RT versus DT relationships during the position task were more negative (p = 0.010) and more positive (p = 0.023), respectively, when compared to the force task. Conclusions: To produce a similar force output, the position task may rely less on the recruitment of relatively high-threshold MUs. Additionally, as the force output decreases, MUs tend to derecruit at a higher force level during the position task.